405 The Effect of a Patient Survey in the Evaluation of Obstructive Sleep Apnea in a High Risk Cardiology Outpatient Population. (3rd May 2021) - Patel, Dev; Patel, Ishan; Cohen, Marc; Patel, Sunil
Abstract: Introduction: Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder. The estimated prevalence is approximately 15 to 30 percent in males and 10 to 15 percent in females. Patients with OSA have an increased propensity for cardiovascular diseases and obesity. Observational studies have demonstrated a consistent association between OSA and hypertension, coronary artery disease, cardiac arrhythmias, and heart failure. The purpose of this study is to evaluate if a patient survey can improve the diagnosis of OSA in a high-risk outpatient cardiac clinic. Methods: In an outpatient cardiac clinic, a retrospective analysis of OSA evaluations was done before and after the use of patient surveys in a high-risk population. The high-risk patient group was defined by the presence of two or more of the following conditions: hypertension, heart failure, cardiac arrhythmias, atrial fibrillation, obesity with a BMI of 30 or more, coronary artery disease, diabetes mellitus, chronic lung disease, history of cerebrovascular accident (CVA), hypothyroidism and chronic renal insufficiency. The patient survey included questions on the presence of daytime sleepiness, presence of snoring, ESS score, choking in sleep, witness apnea, and frequent waking in sleep. Results: During the four months of patient survey use, a total of 143 patients were evaluated as compared to 86 patients in the prior four months without the use of the survey. A significant increase (66.3%) of OSA evaluations was observed during the patient survey period. Conclusion: The use of patient surveys showed a significant improvement in OSA diagnoses in the defined high-risk patient group. Patient surveys might be beneficial to improve the under diagnosis of sleep apnea in high-risk patient populations. Additional research needs to be done to establish the impact of such intervention on patient outcomes. Support (if any):